Study of shear thickening behavior using experimental, mathematical modeling and numerical simulation studies. (2021) - Chauhan, Vimal; Bhalla, Neelanchali Asija; Danish, Mohammad
Abstract: In this paper, the effect of increasing shear rate was studied on the viscosity of shear thickening fluid (STF). It was observed that the viscosity as well as the severity of shear thickening increased with the shear rate. The recovery rate ratio for STF at 25 °C was measured as 88.54% after 30 s, in three interval thixotropy test. Mathematical modeling was also done with the existing viscosity function of STF at 25 °C. It was observed that the viscosity obtained from mathematical model was in good match with the experimental data. For the validation of numerical simulation results, a 3D model of cone and plate was generated in ANSYS FLUENT. A user defined function (UDF) with all the chemical and physical properties of STF was used in 3D model at 25 °C. It was found that STF with UDF depicted similar results as obtained from experimental results, showing shear thinning at low shear rates and shear thickening beyond the critical shear rate. Critical viscosity obtained from experimental, mathematical model and numerical simulation was 0.653 Pa.s at critical shear rate of 10 s −1 . Post shear thickening viscosity of 30.017 Pa.s was achieved for experimental and mathematical model and 30 Pa.s for numerical simulation.